Analisis Kemampuan HOTS Siswa SD Dalam Menyelesaikan Soal IPA - Rohayati, Rafi; Handayanto, Supriyono Koes; Masfufah, Aynin (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to analyze the HOTS ability of elementary school students to solve science questions. The type of research used is descriptive qualitative. The research subjects were 7 class VI students at SDN 2 Ngepoh for the 2023/2024 academic year. Data collection methods were carried out through written tests, documentation, and interviews. The analysis technique used is the Miles & Huberman analysis method. The results showed that Of all 7 class VI  students, there was 1 student who had low ability and was unable to solve HOTS questions on all indicators, 3 students were able to solve HOTS questions on the  evaluating (C5), and 3 students were able to solve HOTS questions on the creating (C6) indicators. This research concludes that the HOTS ability of elementary school students to solve science questions is still low, this is because students are less able to understand concepts so that students have difficulty in solving the problems presented and there is a lack of practice in solving HOTS questions. This research implies the need to improve conceptual understanding and familiarization with HOTS questions in science learning to develop high-level thinking skills in elementary school students.